Achados clínicos, hemodinâmicos e hemogasométricos da infusão contínua de propofol associado ou não ao tramadol em ovelhas submetidas à videolaparoscopia - Lopes, Maristela de Cassia Seúdo [UNESP] (2014)
Twenty four sheep, all female, Santa Ines, age ranged from three to six years and mean weight of 41 ± 4 kg, underwent laparoscopy procedures. The ewe were randomly divided in four groups, designated as GP (propofol), GT1,3 (tramadol 1.3), GT2.6 (tramadol 2,6) and GTepi (epidural tramadol). All ewe were induced with propofol (6.0 mg.kg-1 IV) and anesthesia was maintained with a CRI of propofol (0.5 mg.kg.min-1). Analgesia was obtained with tramadol bolus (1.5 mg kg-1) followed by 1.3 mg kg min-1 CRI (GT1.3, n=6); bolus (3.0 mg kg-1) followed by 2.6 mg kg min-1 CRI (GT2.6, n=6) and by infusion of tramadol epidurally (2.0 mg.kg-1). In a control group recieved saline CRI (GP, n=6). The animals underwent mechanical ventilation Hemodynamic, respiratory and metabolic parameters were evaluated during the preoperative (M0) periods, intraoperative (M15 -M30: dorsal recumbence, M30 to M60: with abdomen insufflation and Trendelemburg positioning and M60 - M90: dorsal recumbence without abdomen insufflation). In the same time, we assessed the quality of induction and recovery from anesthesia, plasma cortisol, degree and duration of analgesia (six hours of post surgical) and use of rescue analgesia in the intra and postoperatively. There were no significant changes in heart rate (HR). The body temperature decreased from M30 until the end of anesthesia (M90) in all groups. The partial pressure of oxygen in arterial blood (PaO2) increased in all groups from M15 as well as the partial pressure of carbon dioxide (PaCO2) from the M30 to M60 in GP and GT1.3, from the M50 to M60 in GT2.6 and in M60 in GTepi. There was a decrease in pH from M30 to M70 in GT1.3, from M40 and M90 in GP and GT2.6 and from M40 to M80 in GTepi. In hemodynamic evaluation, cardiac index (CI) decreased from M30 to M60 in animals GP and GTepi and M15 in GT1.3. In stroke volume (SV) was a reduction from M15 to M60 in GP, GT1.3, GT2.6 and from M30 to M70 in GTepi. The rescue analgesia ...